The preoperative flexion tear gap affects postoperative meniscus stability after pullout repair for medial meniscus posterior root tear - Masanori Tamura; Takayuki Furumatsu; Takahiro Kitayama; Yusuke Yokoyama; Yuki Okazaki; Koki Kawada; Toshifumi Ozaki (Knee Surgery & Related Research)
Abstract Background We investigated whether the preoperative flexion tear gap (FTG) observed in open magnetic resonance imaging (MRI) affects meniscus stability after medial meniscus (MM) posterior root (MMPR) repairs. Furthermore, time-correlated MRI findings from MMPR tear occurrence were evaluated. Methods This retrospective observational study included 54 patients (mean age, 64.6 years; 13 males and 41 females) who underwent pullout repair for radial degenerative MMPR tear. Meniscus stability (scored 0–4 points) was assessed using a semi-quantitative arthroscopic scoring system during second-look arthroscopy 1 year postoperatively. The FTG was evaluated on preoperative axial MRI at 90° knee flexion. Other MRI measurements included MM extrusion (MME) at 10° knee flexion, MM posterior extrusion (MMPE) at 90° knee flexion, and MM posteromedial extrusion (MMpmE) at 90° knee flexion preoperatively and 1 year postoperatively. The correlation between the arthroscopic stability score and MRI findings was investigated. A receiver-operating characteristic curve was calculated to predict a good meniscus healing score (3–4 points). The correlation between the FTG and patient demographics, including time from injury to MRI, was analyzed. Results At 1 year postoperatively, MME increased by 1.1 mm, while MMpmE and MMPE decreased by 0.4 mm and 1.0 mm, respectively. The meniscus stability score was negatively correlated with the preoperative FTG (r = -0.61, p < 0.01). The time from injury to MRI was significantly correlated with the preoperative FTG. The receiver-operating characteristic curve identified an FTG cut-off value of 8.7 mm for predicting good postoperative stability, with sensitivity and specificity of 67% and 85%, respectively. Conclusions FTG evaluated with open MRI at 90° knee flexion was associated with time from injury and affected meniscus stability following pullout repair. MMPR tears should be treated in the early phase to increase meniscus healing stability.